2021
DOI: 10.1208/s12248-021-00645-2
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-Generated Immunomodulatory Nanoparticles and Formulation-Dependent Effects on Lipopolysaccharide-Induced Macrophage Inflammation

Abstract: Nanoparticles (NPs) have emerged as a highly useful and clinically translatable drug delivery platform for vast therapeutic payloads. Through the precise tuning of their physicochemical properties, NPs can be engineered to exhibit controlled drug release properties, enhanced circulation times, improved cellular uptake and targeting, and reduced toxicity profiles. Conventional bulk methods for the production of polymeric NPs suffer from the ability to control their size and polydispersity, batch-to-batch varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…PLG nanoparticles are being investigated as alternative Ag‐carriers that are biodegradable, tunable, and manufacturable at large scale (Pearson, Casey, Hughes, Miller, et al, 2017), (Truong et al, 2021). Ag has been incorporated into NPs by encapsulation, surface conjugation, and as Ag‐polymer conjugates (D. R. Getts et al, 2012; McCarthy et al, 2017; Pearson, Casey, Hughes, Miller, et al, 2017; Tostanoski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PLG nanoparticles are being investigated as alternative Ag‐carriers that are biodegradable, tunable, and manufacturable at large scale (Pearson, Casey, Hughes, Miller, et al, 2017), (Truong et al, 2021). Ag has been incorporated into NPs by encapsulation, surface conjugation, and as Ag‐polymer conjugates (D. R. Getts et al, 2012; McCarthy et al, 2017; Pearson, Casey, Hughes, Miller, et al, 2017; Tostanoski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rational biomaterial selection can also have inherent immune-stimulating or immune-modulating effects. For example, a palmitoyl-based lipid coupled to a peptide Ag can directly upregulate immunity. , PLGA particles have demonstrated the intrinsic ability to prevent DC and macrophage maturation and block immune-stimulating signaling pathways. Rationally conjugating Ags to either lipids or polymers and encapsulating in NPs can provide a versatile tool to expand delivery mechanisms and control desired T cell immunity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Chavez-Santoscoy et al developed a functionalized polyanhydride nanoparticles and found that the nanoparticles initiated the secretion of pro-inflammatory cytokines such as IL-6, IL-1b and TNF-α in alveolar macrophages [260]. Recently, Truong et al developed a high-throughput microfluidic method for the generation of cargo-less immunomodulatory polymeric nanoparticles [261]. In this study, a set of 12 nanoparticles were developed and their ability to modulate the LPS-induced macrophage responses were investigated.…”
Section: Targeting Macrophagementioning
confidence: 99%